Penggunaan Media HAPPY NOTE untuk Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran IPS di SMPN 24 Malang - Muhammad Naufal; Satti Wagistina; Elly Hartatiek; Aulia Isnaeni Fariski (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to determine the effectiveness of using the Happy Note LKPD media in improving students' learning motivation in Social Studies (IPS) for Grade VII at SMPN 24 Malang. The main issue addressed is the low level of student motivation. The research method used is Classroom Action Research (CAR) conducted in two cycles, with a qualitative approach and descriptive method. The subjects were 33 students from class 7E. Data were collected through observation, questionnaires, and interviews. The results show that the use of Happy Note significantly increased students’ learning motivation. In cycle I, 61% of students were in the “Very Good” category, which increased to 86% in cycle II. Additionally, there was a 23% increase in average motivation scores compared to before the treatment. Students demonstrated enthusiasm and active participation during the learning process. This media also fostered a fun learning environment through motor activities such as cutting, pasting, and coloring. The study concludes that Happy Note is effective in enhancing students’ learning motivation. It is recommended that this media be considered an alternative in IPS learning or other subjects requiring a creative and enjoyable approach.